Pengaruh Kompensasi dan Motivasi Kerja Terhadap Kinerja pada Driver Gojek di Kabupaten Karawang - Latif, Muhammad Faris; Suroso; Karnama, Maman Mulya (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study was to find out and explain the effect of compensation and work motivation on the performance of motorcycle taxi drivers in Karawang Regency. This research was conducted using quantitative research methods, with data analysis using multiple linear regression and data collection using a questionnaire or questionnaire. Based on the results of the study, it shows that compensation has a positive and significant effect on driver performance. Work motivation has a positive and significant influence on driver performance. Simultaneously the two variables examined, namely compensation and work motivation have a positive and significant effect on performance. Keywords: Compensation, Work Motivation, Performance.